Traditional seed management and genetic diversity in barley varieties in high-hill agro-ecosystems of Nepal - Bajracharya, J.; Brown, A.H.D.; Joshi, B.K.; Panday, D.; Baniya, Bimal K.; Sthapit, B.R.; Jarvis, Devra I. (Springer, 2012)
Chawali and Lekali are two common farmers barley varieties or landraces in Jumla, Nepal (2,2403,000 m) with small to bold grains and wide adaptation from irrigated low lands to high hills. This study was undertaken to test whether features of the traditional seed system can significantly influence the diversity of a crop and its conservation on-farm. In Jumla (high-hill), the barley seed system is completely informal and is mainly from farmer to farmer. In the present study, the seed flows and the pattern of genetic diversity in barley were investigated to detect differences between the two varieties and test the divergence among populations of each variety These data suggested that Chawali, the more common variety, was less subject to homogenising gene flow between farms than was Lekali. A total of 128 farming households were surveyed for seed supply information and 128 populations for each landrace from two villages: Kartikswami and Talium were collected for SSR diversity analysis. Some 92 SSRs were screened in an initial sample of 20 barley populations of both landraces and 2 improved varieties (LG-51 and Soluwa). Of the 81 SSRs that consistently amplified, only 15 SSRs (19%) were polymorphic with gene diversity values ranging from 0.09 to 0.71. A medium to low diversity was detected among the landrace populations of barley varieties. Chawali populations were less polymorphic within ecological groups, and more divergent between than were Lekail populations. This result accords with Chawali having a more conservative local seed system.